2020
DOI: 10.21037/jtd-20-2363
|View full text |Cite
|
Sign up to set email alerts
|

The public health response to the COVID-19 outbreak in mainland China: a narrative review

Abstract: The COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused nations to adopt unprecedented control measures in order to curb its spread.As the first nation to respond, China's aggressive control measures appeared to have been effective in suppressing the first wave and keeping new cases under control. Here, we provide the historical context and details of China's public health response to COVID-19. We highlight the lessons and impact of the 2002-2003 SARS outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
(15 reference statements)
0
30
0
Order By: Relevance
“…The centralized decision-making, the lack of public debates, and unrestricted powers in authoritarian regimes appeared to contribute to undertaking more expeditious and stringent policy responses. China, for example, rapidly implemented the strictest isolation and control measures, including traffic control of people and monitoring of its citizens to ensure the effectiveness of quarantine efforts (Kang et al (2020); Zanin et al (2020)). The response system implemented in Vietnam, another authoritarian country, included fast reactions in the form of suspending flights from and to epidemic areas, and limiting crowds of people, as well as a strong leadership and a clear policy communication (Ha et al (2020)).…”
Section: Resultsmentioning
confidence: 99%
“…The centralized decision-making, the lack of public debates, and unrestricted powers in authoritarian regimes appeared to contribute to undertaking more expeditious and stringent policy responses. China, for example, rapidly implemented the strictest isolation and control measures, including traffic control of people and monitoring of its citizens to ensure the effectiveness of quarantine efforts (Kang et al (2020); Zanin et al (2020)). The response system implemented in Vietnam, another authoritarian country, included fast reactions in the form of suspending flights from and to epidemic areas, and limiting crowds of people, as well as a strong leadership and a clear policy communication (Ha et al (2020)).…”
Section: Resultsmentioning
confidence: 99%
“…The Chinese multi-sectoral response has been overseen from the beginning by the highest political level [ 33 , 34 ]. By the end of January, intense lockdowns were implemented first in Wuhan, then in the Hubei Province and finally in nearly all of China [ 7 , 31 ]. The lockdowns were accompanied by a very rapid construction of new hospitals in Wuhan, the re-allocation of several thousand medical staff from other parts of China to Hubei Province, intense surveillance and isolation/quarantine measures, and by severe travel restrictions in the whole country [ 7 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…While countries in Europe and the Americas are now waiting for the vaccines, China has demonstrated that SARS-CoV-2 elimination is feasible even in a 1.4 billion population country [ 7 , 16 , 31 ]. Similarly, New Zealand has opted for elimination early on and has been largely successful with this strategy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cities throughout Hubei province (of which Wuhan is capital) announced similar lockdowns over the next few days [1]. The rest of China was subject to social distancing measures: mass transit and public gatherings were severely curtailed, and the New Year holiday (Chunyun) was extended, which kept most schools, workplaces, and businesses closed [1][2][3]. In addition, numerous measures were implemented to rapidly identify and isolate suspected cases.…”
Section: Introductionmentioning
confidence: 99%